Correlation of Quality Parameters with the Baking Performance of Wheat Flours. Issue 4 (23rd July 2014) - Thanhaeuser, Silvia Maria; Wieser, Herbert; Koehler, Peter
ABSTRACT: The baking performance of a set of flours from 13 wheat cultivars was determined by means of two different microscale baking tests (10 g of flour each). In the micro‐rapid‐mix test the dough was mixed for a fixed time at a high speed, whereas the microbaking test used mixing to optimum dough consistency in a microfarinograph. Quality parameters such as sedimentation value, crude protein content, dough and gluten extension data, and microfarinograph data were also determined. Finally, quality‐related protein fractions (gliadins, glutenins, SDS‐soluble proteins, and glutenin macropolymer) were quantitated by extraction/HPLC methods with reversed‐phase and gel‐permeation columns. All quality parameters were correlated with the bread volumes of both baking tests. The results demonstrated that the microbaking test (adapted mixing time) was much more closely related to the quality parameters than the micro‐rapid‐mix test (fixed mixing time), which hardly showed any correlation. Among the standard quality parameters, only the crude protein content showed a medium correlation with the bread volume of the microbaking test ( r = 0.71), whereas the contents of gliadins ( r = 0.80), glutenins ( r = 0.76), and glutenin macropolymer ( r = 0.80) appeared to be suitable parameters to predict the baking performance of wheat flour. All other quality parameters were not or were only weakly correlated and unsuitable for predicting baking performance.